PERBEDAAN PERSEPSI COMPANIONSHIP DALAM PERNIKAHAN ANTARA LAKI-LAKI DAN PEREMPUAN - Fifi Novia; Budi Andayani (Program Studi S1 Psikologi, 2020)
Indonesian’s divorce rate is the highest among countries in Asia-Pacific, with 70% from total cases were submitted by women. Based on BKKBN data, there are 200 thousands divorce cases each year, and over two millions marriages each year. Highest causes of these divorce cases are marital-abuse (physically and emotionally) and infidelity.These causes indicate about failure in maintaining companionship between husband and wife. This research aims to find out whether there are differences of companionship in marriage between men and women. Data were collected online. There were 105 total subjects, 54 men and 51 women. Hypothesis analysis were done with Independent t-test method. Results of this research shown that there is significance differences in companionship between men and women (sig=0,014)